Toward Novel [18F]Fluorine-Labeled Radiotracers for the Imaging of α-Synuclein Fibrils - Uzuegbunam, Bright C.; Li, Junhao; Paslawski, Wojciech; Weber, Wolfgang; Svenningsson, Per; Ågren, Hans; Yousefi, Behrooz Hooshyar (Frontiers in Aging Neuroscience, 2022)
The accumulation of α-synuclein aggregates (α syn) in the human brain is an occurrence common to all α-synucleinopathies. Non-invasive detection of α syn in a living brain with a radiotracer is not yet possible. We have recently discovered that a methylenedioxy group in the structure of diarylbisthiazole (DABTA) based tracers improves binding affinity and selectivity to α-syn. Subsequently, complementary in–silico modelling and machine learning (ML) of tracer-protein interaction were employed to predict surface sites and structure-property rela-tions for the binding of the ligands. Based on this we developed a small focused library of DABTAs from which 4-(benzo[d][1,3]dioxol-5-yl)-4'-(3-[18F]fluoro-4-methoxyphenyl)-2,2'-bithiazole [18F]d2, 6-(4'-(3-[18F]fluoro-4-methoxyphenyl)-[2,2'-bithiazol]-4-yl)-[1,3]dioxolo[4,5-b]pyridine [18F]d4, 4-(benzo [d][1,3]dioxol-5-yl)-4'-(6-[18F]fluoropyridin-3-yl)-2,2'-bithiazole [18F]d6, 6-(4'-(6-[18F]fluoropyridin-3-yl)-[2,2'-bithiazol]-4-yl)-[1,3]dioxolo[4,5-b]pyridine [18F]d8 were selected based on their high binding affinity and further evaluated. Binding assays carried out with the non-radioactive d2, d4, d6 and d8 showed high binding affinity to α-syn: 1.22, 0.66, 1.21 and 0.10 nM respectively as well as excellent selectivity over β-amyloid plaques (Aβ) and microtubular tau aggregates (> 200-fold selectivity). To obtain the tracers, their precursors were radiolabeled either via an innovative ruthenium-mediated reaction ([18F]d2 and [18F]d4) or typical SNAr reaction ([18F]d6 and [18F]d8) with moderate to high radiochemical yields (13 %－40 %), and high molar activity > 60 GBq/μmol. Biodistribution experiments carried out with them in healthy mice revealed that [18F]d2 and [18F]d4 showed suboptimal brain pharmacokinetics: 1.58 and 4.63 %ID/g at 5 min postinjection (p.i.), and 1.93 and 3.86 at 60 min p.i., respectively. However, [18F]d6 and [18F]d8 showed improved brain pharmacokinetics: 5.79 and 5.13 %ID/g at 5 min p.i.; 1.75 and 1.07 %ID/g at 60 min p.i.; and 1.04 and 0.58 %ID/g at 120 min p.i., respectively. The brain uptake kinetics of [18F]d6 and [18F]d8 were confirmed in a dynamic PET study. Both tracers also showed no brain radiometabolites at 20 min p.i. in initial in vivo stability experiments carried out in healthy mice. [18F]d8 seems very promising based on its binding properties and stability, thus encouraging validation of its usefulness as a radiotracer for in vivo visualization of α-syn in preclinical and clinical settings. Additionally, in-silico and ML predicted values correlated with the experimental assays of the ligands.